Analisis Kuantitatif Tar dan Nikotin Terhadap Rokok Kretek Yang Beredar di Indonesia: Analisis Kuantitatif Tar dan Nikotin Terhadap Rokok Kretek yang Beredar di Indonesia - Relita Florentika; Widiyanto Kurniawan (Eruditio : Indonesia Journal of Food and Drug Safety, 2022)
Tar and nicotine are substances contained in cigarettes, which are harmful to health and causes addiction. Nicotine can paralyze the brain and taste, increase adrenaline hormone which affects the heart to beat faster and work harder. Nicotine in respiration system can be rapidly absorbed from the lungs into the blood. The perilous effect of nicotine and tar is stimulating the formation of cancer cells. Based on regulation, tar and nicotine content must be listed on cigarette packages, so people can easily discover it. Aim of this research was to know the tar and nicotine content of kretek cigarettes sold in Indonesia. Sample of this research using cigarettes taken from Yogyakarta, Mamuju, Pontianak, Kupang, Palembang, Manokwari, Sofifi, Jambi, Palangkaraya, Jakarta, Pekanbaru, Palu, Pangkalpinang, Jayapura, Banjarmasin, Kendari, Ambon, Batam, Padang, Mataram and Denpasar. This research is expected to provide general information to the public regarding the suitability and correctness of the nicotine and tar content of cigarettes shown on the packaging. Tar and nicotine content are determined by gas chromatography on the total particulate matter (TPM) obtained from the smoking process using a smoking machine. Result showed that nicotine content was 57,00-152,00% and two brands contained nicotine more than requirement (maximum 120,00%). The tar content ranged from 48,67-151,95% and two brands contained nicotine more than 120,00% of the packaging label.